Self-configuration power scheme for femtocell base station - Peng XU; Xu-ming FANG; Zheng XIANG; Rong HE (Tongxin xuebao)
To solve the issue that new femtocells deployed in hierarchical networks would introduce a series of interference,a power self-configuration scheme was proposed.Various kinds of interference that femtocell base station might receive from other base stations were analyzed.Then an optimal power issue was formulized,as was able to maximize the femtocell system capacity on the condition guaranteeing the existing users'normal communication.And the optimal solution was also obtained with lagrange multiplier method.The simulation results show that the proposed scheme cuts down the transmit power of femtocell,increases the throughput and reduces interference for existing users,comparing with the scheme based on received signal strength.